Phylogenetic Conflict in Bears Identified by Automated Discovery of Transposable Element Insertions in Low-Coverage Genomes. (29th August 2017) - Lammers, Fritjof; Gallus, Susanne; Janke, Axel; Nilsson, Maria A.
Abstract: Phylogenetic reconstruction from transposable elements (TEs) offers an additional perspective to study evolutionary processes. However, detecting phylogenetically informative TE insertions requires tedious experimental work, limiting the power of phylogenetic inference. Here, we analyzed the genomes of seven bear species using high-throughput sequencing data to detect thousands of TE insertions. The newly developed pipeline for TE detection called TeddyPi (TE detection and discovery for Phylogenetic Inference) identified 150, 513 high-quality TE insertions in the genomes of ursine and tremarctine bears. By integrating different TE insertion callers and using a stringent filtering approach, the TeddyPi pipeline produced highly reliable TE insertion calls, which were confirmed by extensive in vitro validation experiments. Analysis of single nucleotide substitutions in the flanking regions of the TEs shows that these substitutions correlate with the phylogenetic signal from the TE insertions. Our phylogenomic analyses show that TEs are a major driver of genomic variation in bears and enabled phylogenetic reconstruction of a well-resolved species tree, despite strong signals for incomplete lineage sorting and introgression. The analyses show that the Asiatic black, sun, and sloth bear form a monophyletic clade, in which phylogenetic incongruence originates from incomplete lineage sorting. TeddyPi is open source and can be adapted to various TE and structural variation callers. The pipeline makes it possible to confidently extract thousands of TE insertions even from low-coverage genomes (∼10×) of nonmodel organisms. This opens new possibilities for biologists to study phylogenies and evolutionary processes as well as rates and patterns of (retro-)transposition and structural variation.